A Critical Thinking Research Trends: A Bibliometric Analysis (2020–2025) - Afifah, Sri Nur; Dahlan, Dadang; Kurniawati, Susanti (Journal of Educational Sciences, 2025)
This study aims to analyze publication trends related to critical thinking over the past five years (2020–2025) using a bibliometric approach. Data were collected from the Scopus database and processed using R  Studio with the Bibliometrix package. The results reveal a significant increase in the number of publications each year, indicating growing scholarly attention to the topic of critical thinking. Leading publication sources include Thinking Skills and Creativity and Educational Sciences: Theory and Practice. Frequently appearing keywords such as “critical thinking,” “education,” and “higher education” highlight the strong connection between critical thinking and the educational domain. Citation network and keyword co-occurrence analyses demonstrate the existence of dominant research clusters, particularly within the context of 21st-century learning. These findings offer insight into the current development trajectory of critical thinking research and provide a foundation for future studies to explore underexamined areas in the field.